STRATEGI KEPALA SEKOLAH DALAM MENGELOLA IKLIM SEKOLAH DI LEMBAGA PENDIDIKAN DASAR - Analisna, Analisna; Umi Zarhasih, Uswatun; Mubarok, Ramdanil; Sadad, Roihan (MPI STAI Sangatta Kutai Timur, 2023)
This research aims to describe the management of school climate, state heads of schools in managing school climate, and challenge the management of school climate in primary education institutions. The method used in this research is the descriptive qualitative research method. The results are: In managing the school climate, the principal formulates ethical values, inspires enthusiasm, adjusts school goals, and fosters commitment, mutual respect and trust, and cooperation. Then, the principal's strategy in managing the school climate is carried out by setting an example, increasing motivation, and increasing discipline, and commitment. Meanwhile, the challenges in managing the school climate are absenteeism, matching the teacher's educational background, and communication between parents and teachers in the learning process.